SOCIALIZATION OF TOURISM WORK METHOD AS A MODERN LEARNING MEDIA IN SMA PGRI KABUPATEN LAHAT - Diana Widhi Rachmawati; Erma Yulaini; Ida Suryani; Imelda Ratih Ayu; Barkudin; Ana Theriana; Diana Luspa (IJCDE (Indonesian Journal of Community Diversity and Engagement), 2021)
Basically, the subject matter taught in schools, especially SMA PGRI Lahat Regency, in subjects is still minimal in enrichment material, especially in lessons at school. So that the results of renewable lecturers' research can be used as additional material through socialization with teachers and students. The theme of this activity is "socialization of the field trip method as a modern learning medium at SMA PGRI Labupaten Lahat". The resource persons for this activity were Erma Yulaini S.Pd., M.Si, Ana Theriana, M.Pd, Ida Suryani, M.Pd, Barkudin, M.Pd, Diana Widhi Rachmawati M.Pd, Imelda Ratih Ayu, M. Pd, Dana Luspa, M.Pd. the activity has been carried out for 2 days using 4-5 hours a day, continued tomorrow. The presenters will deliver the material for 5-10 minutes and after that a question and answer discussion is held with the PkM participants, with the aim that the participants, both teachers and students, can understand and know the content of the material presented, increase knowledge, and can also make additional material in the subject. The next activity is the provision of information and promotion of study programs at the University of PGRI Palembang, with the hope that PkM participants can know and understand academic and non-academic activities and invite them to join as part of the students of the University of PGRI Palembang. The method used in this activity is to conduct initial observations of the location of the activity, re-confirm to the school to determine the time and place of PkM implementation, carry out activities such as giving lectures, implementing promotions. at the same time evaluating activities by providing guidance either directly or indirectly to teachers and students regarding the application of teaching materials from the results of the socialization that has been carried out and finally closing